Reconciliation: Facilitating ethical space between Indigenous women and girls of a drum circle and white, Settler men of a police chorus - Laurila, Kelly (Scholars Commons @ Laurier, 2019)
Abstract The purpose of this dissertation was to seek understanding of how a singing partnership between Indigenous women and girls of a drum circle and white, Settler men of a police chorus (i.e., representing public relations for Waterloo Regional Police Services)[1] has been sustained within a local context for five years. Knowing the historical and ongoing colonial systemic violence in policing practices with Indigenous peoples in Canada, it seems unlikely that such a partnership would take place. Song provided this partnership with a bridge for engagement and a means to disrupt enduring perceptions of one another that have fuelled ongoing violence. Through engagement, an ethical space was created that enabled dialogue and understanding of one another, and a critical consciousness of the need for ideological systemic change in policing policies and practices. This singing partnership was the bridge that enabled passageway beyond singing to discussions and engagement with the local police chief and police services. Centering an Indigenous research framework, Indigenous knowledge, methodology and methods were used in this qualitative research study. Indigenous philosophy of wholism and interconnectedness were overarching themes that guided the research process and analysis of participants’ stories. An emergent and central theme was the importance of the shared values of: love, respect, truth, honesty, courage, humility, and wisdom. These values (or sacred teachings of the Anishinaabe[2] peoples) were found to be what underpinned the ethical space that enabled a sustained engagement with one another. [1] It is important to note that each time I use the words, “police chorus,” I have included, in brackets, “representing public relations for Waterloo Regional Police Services.” The purpose of my efforts to repeat this message is to guard against perceptions that Waterloo Regional Police Male Chorus consists only of police officers. In reality, most of the chorus consists of non-Indigenous, white, Settler, ...